Laboratory-scale evaluation of composite spiked samples for erwinia amylovora detection in asymptomatic plants - Catalá-Senent, J. F.; Penyalver, Javier; Navarro, Luis; Baranauskaite, L.; Gorris, María T.; López, María M.; Marco-Noales, Ester (Springer, 2020)
Erwinia amylovora, the fire blight pathogen, can survive in plants and produce latent infections that can lead to false negative results in routine diagnostic procedures, since the pathogen can be present at very low numbers under the detection limit of available techniques. A protocol combining different techniques included in the EPPO diagnostic standard for E. amylovora (2013) was designed in order to determine the minimum amount of plants necessary for detecting the pathogen in asymptomatic plant material. To this aim, single samples of flowers and shoots from pear, apple, and loquat were spiked with an E. amylovora strain at different concentrations, and then analyzed by isolation, real-time PCR and ELISA-DASI. Thereafter, using the single spiked samples that were positive for any of the techniques used, composite spiked samples were prepared by adding to single spiked samples increasing amounts of plant material. Interestingly, whole results show that the most robust technique, less affected by the amount of plant material, was the real-time PCR after enrichment, since 101 -102 cfu ml-1 of E. amylovora could be detected in most cases, both in flowers and in shoots, regardless of the amount of simulated plants analyzed, 3, 5, 10 or 20. The enrichment was confirmed as a necessary step in the analysis of bulked samples to achieve a greater sensitivity. This study is a relevant contribution for programs of extensive screening surveys for prevention of fire blight disease, since it shows that samples can be processed as a pool, improving the detection of E. amylovora in asymptomatic samples.